Om flickors inflytande i skolan - Öhrn, Elisabeth (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
Drawing upon a study of gender, power and resistance in grade nine, this paper focuses on girls' attempts to exert influence in school. Previous research usually describes such behaviour as more frequent among boys. In the class described here however, girls are those acting openly in order to have an influence and pursue their principles. The result point to the girls' small group interaction as vital to these collective actions. Contrary to some studies which point to the small group practice as more or less detrimental to collective actions it seems here to be the very basis of the girls' activities.